Virtual Practicum Guideline Development Based on 5E Learning Cycle - Dewi Handayani; Salastri Rohiat; Muzanip Alperi; Isnaini Safitri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
The research purpose was to develop chemistry practicum guidelines based on the 5 E (Engagement, Exploration, Explanation, Elaboration, Evaluation) learning cycle and determine the student's responses. This development research adapted from Borg and Gall model. Data were obtained from interviews, validation questionnaires from content and media experts, readability questionnaires, and student's responses after used the product. Results validation of the chemistry practicum guidelines shows that the content expert validation scores 4.42 while media expert validation scores 4.65 with a range> 4.2, classified as very good. The average readability test showed a score of 4.28. A product trial to determine the student's response toward developed guidelines had an average of 4.28, which was included in an exciting classification. There was an increase in student learning outcomes with average pretest scores of 50, average posttest scores of 85, and the N-gain value data obtained was 0,7 in the high category. Thus, the study concluded that the chemistry learning guidelines with salt hydrolysis topic based on the 5E learning cycle using the virtual program developed in this study were feasible to be applied in the learning process.